Hello there. To solve this question, we'll simply have to make x => x + 5 in the function.
Given the function:
![f(x)=4x^2-3^{}](https://tex.z-dn.net/?f=f%28x%29%3D4x%5E2-3%5E%7B%7D)
We have to determine f(x + 5)
By making x => x + 5 in this function, we get:
![f(x+5)=4\cdot(x+5)^2-3](https://tex.z-dn.net/?f=f%28x%2B5%29%3D4%5Ccdot%28x%2B5%29%5E2-3)
Now remember the binomial expansion of order 2:
![(a+b)^2=a^2+2ab+b^2](https://tex.z-dn.net/?f=%28a%2Bb%29%5E2%3Da%5E2%2B2ab%2Bb%5E2)
Therefore we have:
![f(x+5)=4\cdot(x^2+2\cdot x\cdot5+5^2)-3](https://tex.z-dn.net/?f=f%28x%2B5%29%3D4%5Ccdot%28x%5E2%2B2%5Ccdot%20x%5Ccdot5%2B5%5E2%29-3)
Multiply the terms inside parentheses and calculate the square.
![f(x+5)=4\cdot(x^2_{}+10x+25)-3](https://tex.z-dn.net/?f=f%28x%2B5%29%3D4%5Ccdot%28x%5E2_%7B%7D%2B10x%2B25%29-3)
Apply the distributive property
![f(x+5)=4x^2+4\cdot10x+4\cdot25-3](https://tex.z-dn.net/?f=f%28x%2B5%29%3D4x%5E2%2B4%5Ccdot10x%2B4%5Ccdot25-3)
Multiply and add the numbers
![\begin{gathered} f(x+5)=4x^2+40x+100-3 \\ \boxed{f(x+5)=4x^2+40x+97} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20f%28x%2B5%29%3D4x%5E2%2B40x%2B100-3%20%5C%5C%20%5Cboxed%7Bf%28x%2B5%29%3D4x%5E2%2B40x%2B97%7D%20%5Cend%7Bgathered%7D)
This is the answer we're looking for.
A way of showing this is the correct answer is to make x = 1 and x = 6 in the former function:
![\begin{gathered} f(1)=4\cdot1^2-3=4\cdot1-3=4-3=1 \\ f(6)=4\cdot6^2-3=4\cdot36-3=144-3=141 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20f%281%29%3D4%5Ccdot1%5E2-3%3D4%5Ccdot1-3%3D4-3%3D1%20%5C%5C%20f%286%29%3D4%5Ccdot6%5E2-3%3D4%5Ccdot36-3%3D144-3%3D141%20%5Cend%7Bgathered%7D)
Then making x = 1 in the expression we found after:
![f(1+5)=f(6)=4\cdot1^2+40\cdot1+97=4+40+97=141](https://tex.z-dn.net/?f=f%281%2B5%29%3Df%286%29%3D4%5Ccdot1%5E2%2B40%5Ccdot1%2B97%3D4%2B40%2B97%3D141)
As expected.